2016
DOI: 10.3390/nano6040068
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanomaterial Uptake from Soil Is Not Increased by Arbuscular Mycorrhizal Colonization of Solanum Lycopersicum (Tomato)

Abstract: Bioaccumulation of engineered nanomaterials (ENMs) by plants has been demonstrated in numerous studies over the past 5–10 years. However, the overwhelming majority of these studies were conducted using hydroponic systems and the degree to which the addition of the biological and chemical components present in the soil might fundamentally alter the potential of plant bioaccumulation of ENMs is unclear. Here, we used two genotypes of Solanum lycopersicum (tomato), reduced mycorrhizal colonization (rmc), a mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These findings demonstrated that mycorrhizal colonization can decrease Ag accumulation in Ag NP-exposed plants and moderate changes in expression level of membrane transport proteins that are possibly involved in Ag uptake. Judy et al (2016) demonstrated that AM fungi did not play a significant role in the transfer of Au NPs to tomato plants. Au NPs accumulated at the rhizoplane of plants that developed a robust (about 35%) AM fungal colonization, suggesting a low toxicity of Au NPs for AM fungi and their possible protective effects on plants.…”
Section: Benefits Of Mycorrhizal and Rhizobial Symbioses For Plants Ementioning
confidence: 96%
“…These findings demonstrated that mycorrhizal colonization can decrease Ag accumulation in Ag NP-exposed plants and moderate changes in expression level of membrane transport proteins that are possibly involved in Ag uptake. Judy et al (2016) demonstrated that AM fungi did not play a significant role in the transfer of Au NPs to tomato plants. Au NPs accumulated at the rhizoplane of plants that developed a robust (about 35%) AM fungal colonization, suggesting a low toxicity of Au NPs for AM fungi and their possible protective effects on plants.…”
Section: Benefits Of Mycorrhizal and Rhizobial Symbioses For Plants Ementioning
confidence: 96%
“…One additional factor, however, may be the interaction of plants with microorganisms which may also affect the uptake and effects of NP. Judy et al [101] found no effects of Au NP (26.5 nm; 25 mg kg 21 ) on arbuscular mycorrhizal fungi (AMF) colonization of Solanum lycopersicum (tomato) plants. Using two genotypes of this plant species, one without mycorrhizal colonization, they also showed that the AMF did not have a role in Au NP uptake from the test soil (pH H 2 O 8.3, 1.4% OC).…”
Section: Exposure and Hazard Assessment Of Enmmentioning
confidence: 99%
“…The interest in alternative materials has increased greatly in soil improvement works [ 9 , 10 ]. Nano-particles have also received special attention due to their unique properties [ 11 , 12 ]. Previous research has shown that nano-particles result in changes to physical, mechanical, and chemical properties.…”
Section: Introductionmentioning
confidence: 99%